Effects of Vitamin D on Skeletal Muscle and Athletic Performance. Issue 8 (15th April 2018) - Abrams, Geoffrey D.; Feldman, David; Safran, Marc R.
Abstract : Vitamin D is known to be important for calcium homeostasis and bone metabolism. It also has important direct effects on skeletal muscle. Unlike authentic vitamins, which cannot be synthesized in the body, vitamin D is produced in the skin using sunlight. Through its nuclear receptor (ie, vitamin D receptor) located throughout the body, including skeletal muscle, vitamin D initiates genomic and nongenomic pathways regulating multiple actions, including myocyte proliferation and growth. In some studies, vitamin D supplementation has been shown to increase muscle strength, particularly in people who are vitamin D deficient. Higher serum levels of vitamin D are associated with reduced injury rates and improved sports performance. In a subset of the population, vitamin D appears to play a role in muscle strength, injury prevention, and sports performance.